Production of antifungal iturins from vegetable straw: A combined chemical-bacterial process. (June 2023) - Yuan, Yuan; Chu, Depeng; Fan, Jiajun; Cui, Zhenzhen; Wang, Rui; Zhang, Han; You, Xiangwei; Li, Yiqiang; Wang, Xiaoqiang
Graphical abstract: Highlights: A combined chemical-bacterial process was developed. Hydrolysate from pepper straw was directly used by Cas02 without detoxification. Extract with strong antifungal activity achieved by macroporous resin purification. 1.58 g iturin-rich extract containing 259.22 mg/g iturin was obtained from 100 g straw. Pepper straw is a promising feedstock for iturin production by B. amyloliquefaciens. Abstract: A combined chemical-bacterial process was developed to convert vegetable straw waste to high value antifungal iturins. Straws from three widely cultivated vegetable (cucumber, tomato and pepper) were evaluated as feedstocks for iturin production. Microwave assisted hydrolysis with very dilute acid (0.2% w/w H2 SO4 ) achieved efficient reducing sugar recovery. The high glucose concentration in non-detoxified hydrolysate from pepper straw facilitated the optimal growth of Bacillus amyloliquefaciens strain Cas02 and stimulated the production of iturin. The fermentation parameters were optimised to enhance the iturin production efficiency. The obtained fermentation extract was further purified using macroporous adsorption resin, resulting in an iturin-rich extract that exhibited strong antifungal activity against Alternaria alternata with an IC50 of 176.44 μg/mL. Each iturin homologue was identified using NMR. Overall, 1.58 g iturin-rich extract containing 164.06 mg/g iturins was obtained from 100 g pepper straw, illustrating the great potential of valorising pepper straw via this process.